Efektivitas Fungisida dan Cuka untuk Sterilisasi Eksplan Sirih Hitam (Piper betle L. var Nigra) - Kuswandi, Paramita Cahyaningrum; Prasetya, Fajar (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Black betel (Piper betle L. var. Nigra) can be found in Indonesia and has been proven to have antimicrobial activity so it has the potential to be used as a medicinal plant. Tissue culture can be used to produce seeds that are the same as the parent plant in large, uniform quantities and to produce secondary metabolites from cell suspension cultures. The sterilization method is a very important initial stage for in vitro plant growth, so optimizing sterilization is the aim of this research. The planting materials used are black betel leaves and nodes. Optimization of the sterilization method was carried out using variations in materials and sterilization time duration. The ingredients used were dish soap, bactericide, fungicide, sodium hypochlorite solution, vinegar, alcohol, and Plant Preservative Mixture (PPM). The medium for leaf explants is MS with 2,4-D and for nodes was MS with BAP. Data on the number of contaminated explants were analyzed using the SPSS program. The results of analysis of variance (ANOVA) showed that the optimal sterilization of black betel leaves was using a fungicide solution for 30 minutes, 5% sodium hypochlorite solution for 10 and 15 minutes, vinegar for 7 minutes, 70% alcohol for 10 minutes and PPM for 1 minute with a 22.1% of explants contaminated. Sterilization by rubbing the nodes under running water and the use of vinegar to sterilize black betel nodia resulted in a significantly lower percentage of contamination (73.3%, P<0.05) compared to the method where the leaves were not cleaned by rubbing under running water and no vinegar.